The Factors Affecting the Interest in Taking Mekaar Loans (Empirical Study on SMEs in Dagang Kerawan Village) - Windani, Amanda Syafira; Simbolon, Ramadona; Lubis, Farida Khairani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the factors that influence the community's interest in taking out Mekaar loans for SMEs in Dagang Kerawan Village. Three factors examined in this study are financial literacy, credit requirements, and credit access. The study employs multiple linear regression analysis to test the impact of these three variables on the community’s interest. The results show that financial literacy (X1) has a significant impact on the public’s interest in accessing Mekaar financing. The higher the community's understanding of financial concepts such as interest, installments, and business management, the greater their interest. The ease, speed, and lack of bureaucracy in credit requirements (X2) also significantly influence, encouraging the public to access financing by fostering a sense of trust. Additionally, credit access (X3), which includes convenient locations, information, and direct approach by Mekaar officers, is a dominant factor in increasing community interest. Overall, these three independent variables were found to have a significant impact on the public's interest in choosing Mekaar financing, with each variable’s significance value being less than 0.05. This study recommends strengthening financial literacy, simplifying credit procedures, and improving accessibility to credit services as strategic steps to enhance community participation in the Mekaar program.